2002
DOI: 10.1248/bpb.25.446
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rat Aortic Fragment within Collagen Gel as an Angiogenesis Model; Capillary Morphology may Reflect the Action Mechanisms of Angiogenesis Inhibitors.

Abstract: Angiogenesis, the formation of new blood vessels from pre-existing vessels, occurs physiologically during embryonal development, tissue injury and inflammation. It is also well known to play an important role in several pathological conditions, such as cancer, diabetic retinopathy, rheumatoid arthritis and atherosclerosis.1) An understanding of the angiogenic process may lead to new therapies for the above diseases, and some angiogenesis inhibitors are already under clinical study as anti-cancer drugs.2)The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…13) There are additional evidences that VEGF differentiates CD34 Ϫ , VE-cadherin Ϫ multipotential adult progenitor cell into CD34 ϩ , VE-cadherin + cell in vitro 38) and that VEGF increases to initiate the process of vascularization by stimulating chemoattraction and proliferation of CD34 ϩ cells such as angioblast and endothelial cell although VEGF alone is not sufficient to direct blood vessel organization and/or maturation. [39][40][41] These evidences suggest that VEGF and TNFa play a role for CML-facilitated proliferation of CD34 ϩ cells during the course of diabetes.…”
Section: Discussionmentioning
confidence: 94%
“…13) There are additional evidences that VEGF differentiates CD34 Ϫ , VE-cadherin Ϫ multipotential adult progenitor cell into CD34 ϩ , VE-cadherin + cell in vitro 38) and that VEGF increases to initiate the process of vascularization by stimulating chemoattraction and proliferation of CD34 ϩ cells such as angioblast and endothelial cell although VEGF alone is not sufficient to direct blood vessel organization and/or maturation. [39][40][41] These evidences suggest that VEGF and TNFa play a role for CML-facilitated proliferation of CD34 ϩ cells during the course of diabetes.…”
Section: Discussionmentioning
confidence: 94%
“…Ectopic expression of RUNX2 supports these observations since RUNX2 overexpression increased cell growth, DNA synthesis, in vitro cell sprouting, and resistance to TGFb 1 in BAEC transfectants relative to control cells. EC within aortic sprouts secrete plasminogen activators and metalloproteinases, mediate degradation of the ECM during vascular sprouting, and respond to angiogenic cytokines such as VEGF (Nicosia and Ottinetti, 1990;Hiraoka et al, 1998;Hata-Sugi et al, 2002). Previous observations from our laboratory showed that the expression of uPA and MT1-MMP was downregulated in EC transfected with dominant-negative Runt, which inhibited endogenous RUNX2 transcriptional activity (Sun et al, 2001).…”
Section: Alternatively Spliced Runx2 and Angiogenesismentioning
confidence: 96%
“…Quantitative assessment used an MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2H-tetrazolium) assay to measure the relative number of viable cells growing from the aorta rings. After removal of the ring of aorta, 300 ml freshly prepared solution containing 100 mg MTS and 1 mg PMS (phenazine methosulfate) in DPBS was added to each well and incubated for 24 h at 37 C. The medium used for this study preferentially selects for endothelial out-growth, but cell number will include some fibroblasts and smooth muscle cells (Hata-Sugi et al 2002).…”
Section: Establishment Of Rat Aorta Culturementioning
confidence: 99%